Angkola Swear Words - Siregar, Elitaria Bestri Agustina; Maria Ulfa; Mhd. Pujiono (Technium Social Sciences Journal, 2021)
This study focuses on the types of theme of swear words in Angkola language, their usage functions and their intended use. This research is a qualitative research. Method used is participant-observation method. Finding reveals that based on their references, swear words in the Angkola community use nine themes, namely, religion, scatology, genitalism, profession, mental and physical abnormality, death, motherhood, animals, body parts, and supernatural beings. There are two functions of Angkola swear words: as a form of expression of anger / annoyance and as a form of intimacy / greeting.